The potential of bike desks to reduce sedentary time in the office: a mixed-method study. (March 2017) - Torbeyns, T.; de Geus, B.; Bailey, S.; Decroix, L.; Meeusen, R.
Abstract: Objectives: To investigate the use of bike desks in an office setting and office workers' experiences of bike desks. Study design: Mixed-method study; quantitative data of cycling desk use in combination with qualitative data of users' experience were obtained via questionnaires. Methods: Bike desks were provided in an office setting during a five-month period. The amount of cycled time, distance and the cycling intensity were registered. At the end of the intervention period, participants filled out a questionnaire about their experiences of cycling desks in the office. Results: Participants cycled for approximately 98 min/week. Most participants were very positive about their bike desk experience and almost all of them would continue using them. About one third of the participants experienced a positive effect on attention and work performance and for about two thirds it positively influenced their motivation during work. Furthermore, about half of the participants felt more energetic, more self-confident and perceived a positive effect on their health and lifestyle. Conclusions: Providing bike desks in an office reduces office workers sedentary time. Furthermore, people experienced positive effects on several personal and work-related parameters. Therefore, providing bike desks in office settings seems to be a promising means to reduce sedentary time. Highlights: Participants cycled for approximately 98 min/week. Most participants spoke positively about the bike desk and would continue using them. People experienced a positive effect on attention, motivation and work performance. Participants felt more energetic and more self-confident. The intervention positively influenced participants' lifestyle.